Level of visual geometry skill towards learning style Kolb in junior high school - Anwar Anwar; Turmudi Turmudi; Dadang Juandi; Saiman Saiman; Muhammad Zaki (Universitas Hamzanwadi, 2023)
This study aims to conduct an in-depth analysis of the visual thinking level of junior high school students with the learning style of assimilators, converges, accommodators, and divergers in solving geometry problems. The type of research used is qualitative research with a grounded theory and case study design. The subjects studied were junior high school students consisting of 6 of 56 students. Data were collected through a learning style inventory (LSI) test given to 56 students to group participants based on the learning style of the Kolb model, then a geometry problem-solving test and interviews were given to 6 students, namely two assimilator students, one converges, one accommodator, and two diverger students. The analysis is based on data from written test results and interviews. Then, time triangulation is carried out to obtain valid research data. The analysis was conducted based on data from written test results and interview results paired with video recordings. Then, triangulation of time is carried out to obtain valid research data. The results of the analysis showed that assimilator students and converger students were able to achieve at the global visual level, namely being able to carry out visual thinking activities well in solving problems, illustrate the problem correctly in geometric drawings/objects, represent problems in mathematical symbols precisely and can express relationships between images well. While accommodator and diverger students can only reach the local visual level, they have yet to be able to show every visual thinking activity well in solving geometry problems, illustrating problems in geometry drawings that could be more precise, and solving rudimentary geometry problems.